Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_121_130
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat Treatment and Microstructure Variations on Disk Superalloy Properties at High Temperature

Abstract: The effects of heat treatment and resulting microstructure variations on high temperature mechanical properties were assessed for a powder metallurgy disk superalloy LSHR. Blanks were consistently supersolvus solution heat treated and quenched at two cooling rates, than aged at varying temperatures and times. Tensile, creep, and dwell fatigue crack growth tests were then performed at 704°C. γ ′ precipitate microstructures were quantified. Relationships between heat treatment-microstructure, heat treatment-mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…As a consequence, all the supersolvus HT lead to higher creep strengths. The beneficial effect of high cooling rates on the creep resistance has been reported in many studies [2,3,6,7]. This trend is confirmed when comparing the creep behaviour of the SUPER and the SUPER-FC HT specimens.…”
Section: Creep-rupture Behavioursupporting
confidence: 71%
“…As a consequence, all the supersolvus HT lead to higher creep strengths. The beneficial effect of high cooling rates on the creep resistance has been reported in many studies [2,3,6,7]. This trend is confirmed when comparing the creep behaviour of the SUPER and the SUPER-FC HT specimens.…”
Section: Creep-rupture Behavioursupporting
confidence: 71%
“…Fatigue is one of the most critical properties for turbine disk alloys, and because superalloy disk materials are mostly free of any extrinsic defects, the grain structure has a significant influence on fatigue properties. [1][2][3][4][5][6][7][8] However, there is a lack of understanding of how the grain structure evolves throughout the complicated thermomechanical processing of superalloys. Powder metallurgy (P/M) processing of superalloys requires consolidation, usually by extrusion, followed by subsequent isothermal forging.…”
Section: Introductionmentioning
confidence: 99%
“…[41] It has been reported that the dwell fatigue performance of Ni-base superalloys can be improved by increasing Cr content, [89,90] volume fraction of c¢, [89] and the size of tertiary c¢ precipitates. [41,91,92] The improvements by increasing Cr content and tertiary c¢ size are qualitatively illustrated in Figure 10(a). One possible explanation for these microstructural and alloying effects may be the increase in transformation toughening and the K th value by increasing Cr contents on the basis that increasing the Cr content of the Ni-base alloy is likely to promote the formation of Cr 2 O 3 .…”
Section: ½20mentioning
confidence: 69%
“…One possible explanation for these microstructural and alloying effects may be the increase in transformation toughening and the K th value by increasing Cr contents on the basis that increasing the Cr content of the Ni-base alloy is likely to promote the formation of Cr 2 O 3 . Similarly, increasing the tertiary c¢ size is likely to promote stress relaxation at the cracktip, [91,92] which would delay fracture of the oxide and increase the apparent K th . In addition, the larger tertiary c¢ size may also promote the formation of Al 2 O 3 by Al from tertiary Ni 3 Al at or near grain boundaries.…”
Section: ½20mentioning
confidence: 99%